Within-breath oscillometry for identifying exercise-induced bronchoconstriction in pediatric patients reporting symptoms with exercise - Barreto, Mario; Veneroni, Chiara; Caiulo, Mariaclaudia; Evangelisti, Melania; Pompilio, Pasquale Pio; Mazzuca, Maria Cristina; Raponi, Giorgia; Pagani, Jacopo; Parisi, Pasquale (Frontiers in Pediatrics, 2024)
Background Evaluating oscillometry parameters separately for the inspiratory and expiratory breath phases and their within-breath differences can help to identify exercise-induced bronchoconstriction (EIB) in pediatric outpatients disclosing exercise-induced symptoms (EIS). Aims To assess the response in impedance parameters following an exercise challenge in patients reporting EIS. Methods Sixty-eight patients reporting EIS (34 asthmatics and 34 suspected of asthma, age mean = 10.8 years, range = 6.0–16.0) underwent an incremental treadmill exercise test. Spirometry was performed at baseline and 1, 5-, 10-, 15-, and 20-min post exercise. Oscillometry was performed at baseline and at 3- and 18-min post exercise. Bronchodilator response to 200 µg albuterol was then assessed. EIB was defined as a forced expiratory volume in 1 s (FEV1) fall ≥10% from baseline. Expiratory and inspiratory resistance (Rrs) and reactance (Xrs), their z-score (Ducharme et al. 2022), and their mean within-breath differences (ΔRrs = Rrsexp-Rrsinsp, ΔXrs = Xrsexp-Xrsinsp) were calculated. Receiver operating characteristic (ROC) curves and their areas (AUCs) were used to evaluate impedance parameters’ performances in classifying EIB. Results Asthmatic patients developed EIB more frequently than those suspected of asthma [18/34 (52.9%) vs. 2/34 (5.9%), p < 0.001]. In the 20 subjects with EIB, Rrsinsp, Rrsexp, Xrsinsp, and Xrsexp peaked early (3’), and remained steady except for Xrsinsp, which recovered faster afterward. ΔXrs widened 18 min following the exercise and reversed sharply after bronchodilation (BD) (−1.81 ± 1.60 vs. −0.52 ± 0.80 cmH2O × s/L, p < 0.001). Cutoffs for EIB leading to the highest AUCs were a rise of 0.41 in z-score Rrsinsp (Se: 90.0%, Sp: 66.7%), and a fall of −0.64 in z-score Xrsinsp (Se: 90.0%, Sp: 75.0%). Accepting as having “positive” postexercise oscillometry changes those subjects who had both z-scores beyond respective cutoffs, sensitivity for EIB was 90.0% (18/20) and specificity, 83.3% (40/48). Conclusion Oscillometry parameters and their within-breath differences changed markedly in pediatric patients presenting EIB and were restored after the bronchodilator. Strong agreement between z-scores of inspiratory oscillometry parameters and spirometry supports their clinical utility, though larger studies are required to validate these findings in a broader population.